Utilización de apósitos antimicrobianos con polihexametileno de biguanida en heridas que no cicatrizaron por primera intención en caninos - Martínez Llerena, Gabriela Estefanía (2022)
wound is the disruption of the continuity and integrity of the tissue that conforms the skin, thus the present research has as objective; To use antimicrobial dressings with polyhexamethylene biguanide in wounds that did not heal by first intention in canines, carried out in the Veterinary clinic of the State University of Bolivar, which is located in the city of Guaranda and is located at 2650 meters above sea level, methodologically the development of the wound healing process was analyzed in 20 canines of which the influence of age was evaluated, sex, breed, body condition, pain scale, size of the canines, diameter, length and depth of the wound, contamination of the wound, alterations present in the hematological biometry and alterations in the glycemia, on the healing variable, measuring the process of superficial closure and complete closure (granulation, proliferation and healing). Obtaining as results that the average time of healing with the application of polyhexamethylene biguanide dressings was 18.8 days, also when evidencing the influence that age and sex have on this physiological process, it was determined that male dogs tend to present the healing process faster than females, in question of breeds no differences were evidenced, in the case of age the dogs older than 5. 1 years old showed that the scarring process can be prolonged in comparison with the other patients, concluding in such a way that the application of the dressing in study has a direct influence in 43.22% on the scarring process and the remaining 56.78% is influenced by other factors such as; the body condition, the care provided by the owners, the age of the patients, base pathologies, among others.